Factors Predicting Recurrence of Clostridium difficile Infection (CDI) in Hospitalized Patients: Retrospective Study of More Than 2000 Patients. Issue 5 (1st June 2015) - Abdelfatah, Mohamed; Nayfe, Rabih; Nijim, Ala; Enriquez, Kathleen; Ali, Eslam; Watkins, Richard R.; Kandil, Hossam
Abstract : Background: Clostridium difficile infection (CDI) has increased in incidence and severity worldwide, causing direct costs estimated to range from US $3.2 billion to $4.8 billion. The aim of this study was to investigate and identify factors that predict recurrence of CDI. Methods: This was a retrospective case-control study between 2007 and 2013 on patients admitted with CDI. Recurrent CDI is defined as a new episode of diarrhea within 90 days confirmed by a positive stool C. difficile toxin assay or polymerase chain reaction, after resolution of the initial CDI episode for at least 10 days and after discontinuation of the CDI therapy. Results: Three thousand twenty patients were diagnosed with CDI between January 2007 and December 2013. Two hundred nine of 2019 patients in the study had a recurrence of CDI within 90 days of the end of the initial CDI episode (10.3%). Multivariate analysis showed that most of the recurrences occurred in patients with comorbidities, particularly chronic kidney disease (odds ratio, 1.3; 95% confidence interval [CI], 1.0–2.4; P = 0.039). In addition, a higher percentage of patients in the recurrence group were prescribed proton-pump inhibitors (odds ratio, 1.65; 95% CI, 1.0–1.7; P = 0.002) and steroids (odds ratio, 1.65; 95% CI, 1.0–1.5; P = 0.047). Conclusions: Our data suggest that the use of glucocorticoids, use of proton-pump inhibitors, and having end-stage renal disease are significant risk factors associated with recurrent CDI.